Solving Metaphor Theory's Binding Problem: An Examination of "Mapping" and Its Theoretical Implications. (2nd January 2016) - Strack, Daniel C.
ABSTRACT: While metaphor researchers commonly use the word "mapping" in explanations of various types of figurative language, there is a lack of recognition that the term is itself metaphorical. In fact, the term has two metaphor-based working definitions, the more commonly cited being that relating to mathematical set theory and the less common definition originating in cognitive neuroscience. Perhaps not coincidentally, terminological inconsistencies relating to mapping have led to theoretical problems both for single-domain theories of metonymy and attempts to examine Lakoff's invariance hypothesis. This article will assert that expressing metonymic connectivity using the neuroscience term "binding" will both eliminate unnecessary theoretical confusion for cognitive linguists and provide common terminology to facilitate productive communication between cognitive linguists and cognitive neuroscientists.